The original function undergoing the transformation is:
[tex]f(x)=\frac{1}{4}^x[/tex]
This function is shown below:
The function is transformed by reflecting it over the x-axis and shifting downwards by 2 units.
Reflection over the x-axis has the rule:
[tex]f(x)\to-f(x)[/tex]
Therefore, the function becomes:
[tex]f^{\prime}(x)=-\frac{1}{4}^x[/tex]
Shifting downwards by 2 units has the rule:
[tex]f(x)\to f(x)-2[/tex]
The new function becomes:
[tex]f^{\prime}(x)=-\frac{1}{4}^x-2[/tex]
To check if the function represents the transformation, we can use the provided point:
[tex]\begin{gathered} (x,y)=(-1,-6) \\ \therefore \\ -6=-\frac{1}{4}^{-1}-2 \\ -6=-4-2 \\ -6=-6(True\text{)} \end{gathered}[/tex]
Therefore, the transformed function is:
[tex]f^{\prime}(x)=-\frac{1}{4}^x-2[/tex]
[tex]-2[/tex]